Cary J. Nederman: Worlds of Difference: European Discourses of Toleration, C. 1100- C. 1550. The Pennsylvania State University Press, University Park, Pennsylvania. - Ballacci, Giuseppe (Foro Interno, 2004)
Sin resumen